Isolation and Characterization of Chitinolytic Bacteria and Their Potential to Inhibit Plant Pathogenic Fungi - DWI SURYANTO; NETTI IRAWATI; ERMAN MUNIR (Indonesian Society for microbiology, 2011)
A study on the isolation and characterization of chitinolytic bacteria and their potential to inhibit plant pathogenic fungi has been done. The bacteria were isolated from the soil of Karo, Langkat, and Bangka, Sumatra. Ganoderma boninense, Fusarium oxysporum, and Penicillium citrinum of the stock cultures in Laboratory of Microbiology Faculty of Mathematics and Natural Sciences, Universitas Sumatera Utara were used for growth inhibition assay by the isolated bacteria. KR05 and LK08 shared similar morphological and physiological characters; like wise, KR07 shared property similarities with BK08. All bacterial isolates inhibited the growth of G. boninense F. oxysporum , and P. citrinum at a different extent. LK08 showed the highest inhibition rate followed by BK07 and BK09. However, P. citrinum was inhibited more by BK07 and BK09. The crude enzyme preparation of the latter isolate exhibited the highest chitinase activity. The result suggested that their swarming activity seemed to contributed to inhibition of fungal growth.